Prevenção geral positiva: análise crítica das teorias de Günther Jakobs e Winfried Hassemer - Silva, Lucas Santana (2011)
This analysis is the result of a study about the theoretical foundations of the authors Günther Jakobs e Winfried Hassemer, two renowned criminalists in the stage of the criminal Law doctrine that hold the positive general prevention theory as theory of punishment. The investigation process includes the dogmatic sphere, standing in the line of research of Legal Criminal Systems Contemporary. We depart from the critical study of the theory of punishment of Günther Jakobs, and the theory of penalty of Winfried Hassemer, for then a critical exposition of the common structure of theories, and finally to compare the two theories in their particularities. The research has the objective to infer on the positives and negatives aspects of positive general prevention for the current criminal Law dogmatics, as well as to ascertain whether they are adequate or have some contribution to the contemporary criminal Law, since it is one of the last speeches on the search of a purpose of punishment.